Penggunaan Instagram Terhadap Citra Diri Mahasiswa - Sri Rejeki; Euis Komalawati; Poppy Indriyanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Instagram is one of the social media that has the concept of visual interaction. Various photo and video content on Instagram sometimes triggers and influences people to form a different self-image to their lives in the real world. The purpose of this study was to find out the effect of Instagram use on student self-image. The independent variable is Instagram Usage, and the dependent variable is Self-image. This research uses quantitative methods, with data collection techniques using questionnaires, documentation, and literature studies. The data analysis method uses a validity and reliability test, product-moment, correlation coefficient, determination coefficient, hypothesis test, and simple linear regression test. Data processing using SPSS program version 25.00. The number of respondents was 93 people out of 1230 Communication Management students of the STIAMI Institute. Sampling technique using simple random sampling with Slovin formula. Based on Dramaturgy Theory about self-image, the results also showed in the T-test hypothesis was accepted, and the product-moment correlation test stated there is a significant positive relationship between Instagram use and self-image. The confines determination test results showed that Instagram's effect on self-image has a fairly high percentage. R Square value is 0.638 or 63.8%. With a high percentage value, Instagram users, especially students, should be smarter and wiser to use Instagram. With a positive motive of use, it will not cause a bad self-image of a person.